IMPLEMENTASI PENDIDIKAN KARAKTER DALAM MERESPON KOMPETENSI PESERTA DIDIK ABAD 21 - Zaenudin; Yudin Citriadin; Muammar (Indonesian Journal of Education and Learning, 2023)
Character education will become a program that will be implemented by all levels of education, where in the 21st century many things will occur, including changes in learning models, and changes in sophisticated technology that will cause changes in the way we communicate. This change is balanced with student character education, it needs to be developed with character values ​​not only in the cognitive domain but also at other levels such as affective and psychomotor. This study uses a qualitative approach with a case study type of research. This research was conducted at SMKN 1 Praya Central Lombok. Sources of research data are school principals, vice principals, teachers, and students. Data collection techniques from observation, interviews, and documentation. Data analysis was carried out interactively and took place continuously until the collected data was saturated, the activities in data analysis were data collection, data presentation, and concluding/verifying data condensation. There are four criteria to see the validity of research data, namely: Credibility, Transferability, Dependability, and Confirmability. The results of the study show that the implementation of character education has been well implemented in various fields. This can be seen from the results of the implementation of character education at Praya 1 Public High School, which has been able to respond to the needs of students and develop their potential and interests of students.